A Comparative Analysis of Vocabulary Enrichment Goals in Mechanical Engineering and English Education Programs - Agus Budiarte; Ni Putu Ines Marylena; Putu Wiraningsih; Ryan Puby Sumarta (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study explores the distinction in vocabulary enrichment goals between Mechanical Engineering students and English Education students, using Gardner's socio-educational model, which differentiates between instrumental and integrative motivation. Descriptive quantitative design data were collected by using a 24-item questionnaire among 15 Mechanical Engineering students from Politeknik Pelayaran Sorong and 15 English Education students from UHN I Gusti Bagus Sugriwa Denpasar, through purposive sampling. The findings indicate that Mechanical Engineering students have highly emphasized instrumental motivation in learning vocabulary; it is a useful tool for understanding technical texts, equipment operation, and preparation for industry-related communication. On the other hand, English Education students have higher integrative motivation since, for them, learning vocabulary contributes to the development of better communicative competence, cultural understanding, and professional identity as future educators. These results are consistent with Gardner's (1985) theory, which is further supported by disciplinary literacy perspectives indicating that different fields involve different literacy demands, which become determinants of the learners' interests in vocabulary enrichment. It concludes that academic context and career expectations are strong determinants of learners' goals in vocabulary learning, emphasizing differentiated vocabulary instruction. For this reason, ESP-centered vocabulary teaching will be relevant to the technical students, while the English Education students need to be taught vocabulary in a more communicative way and culturally enriched.